CHARACTERISTICS AND OUTCOME OF PATIENTS WITH DIFFUSE LARGE B CELL LYMPHOMA-TREATED WITH CHEMOTHERAPY OR CHEMO-IMMUNOTHERAPY - Qubtia, Maria; Munawar, Kiran; Hamid, Mustafa Ali; Badar, Farhana; Siddiqui, Neelam; Kazmi, Syed Ather; Hameed, Abdul (Journal of Ayub Medical College Abbottabad, 2016)
Background: Diffuse large-B-cell lymphoma, is the most common subtype of Non-Hodgkin lymphoma. Aim of this study was to look at the characteristics and outcome of DLBCL patients who were treated with chemotherapy or chemotherapy plus rituximab at our institution. Methods: Data of 750 patients, who got registered at our institute between 2007 and 2014, was reviewed retrospectively. After appropriate exclusions, 337 were included. Disease free survival (DFS) and overall survival (OS) were compared between patients who received rituximab plus CHOP (Cyclophosphamide, Doxorubicine, Vincristine, Prednisolon) (R-Ch) and standard chemotherapy-CHOP (S-Ch). Results: Males and females were 216 (64%) and 121 (36%) respectively, with median age 38 years (Range 18-80 yrs.). R-Ch and S.Ch was received by 129(38.3%) and 197(58.4%) patients, respectively. Complete remission (CR) was achieved by 81 (62.8%) vs. 105 (53.3%) patients in R-Ch vs. S-Ch cohorts, respectively. In subset analysis CR was seen in 34 (63.0%) and 45 (58.4%) (p=0.01) in R-Ch/XRT and S-Ch/XRT, respectively. At three years, DFS was 85.3% vs. 74% (p=0.04) and OS was 82.2% vs. 72.6% (p=0.02) in R-Ch and S-Ch cohorts respectively. Deaths observed were 9 Vs.13 in R-Ch/XRT and S-Ch/XRT, respectively. Conclusion: Based on our study, onset of DLBCL is at younger age in our population with male predominance. Addition of rituximab to CHOP resulted in better DFS and OS in patients with DLBCL. In developing countries, due to cost, large number of patients do not have access to rituximab. Efforts should be made to reduce the price of targeted therapies so that more and more patients are benefitted from these newer agents. Keywords:DLBCL, CHOP, Rituximab, DFS, OS